2017
DOI: 10.3389/fpsyg.2017.00384
|View full text |Cite
|
Sign up to set email alerts
|

The Child Attachment Interview: A Narrative Review

Abstract: Attachment theory promoted an impressive body of research on the psychic developmental processes, resulting in studies on both typical and atypical development. Much of the diffusion of the attachment theory in the clinical field was related to the design of reliable instruments to evaluate the organization of attachment in infancy as well as in adulthood. Until recently, the lack of a suitable instrument to assess attachment in middle childhood as well as in adolescence hindered the expansion of research in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 57 publications
(119 reference statements)
2
22
0
Order By: Relevance
“…In contrast, in this sample, only 14% of the CSA-exposed children were classified as having disorganized attachment. Previously, researchers have argued that the disorganized attachment classification is in need of additional investigation in terms of how it manifests in middle childhood in general and as measured on the CAI specifically Fearon, Shmueli-Goetz, Viding, Fonagy, & Plomin, 2014;Privizzini, 2017); for instance, some authors suggest that disorganization may present as dismissing attachment later in development (Fearon et al, 2014;Weinfeld, Whaley & Egeland, 2004). However, given the limited number of studies on this topic, at this point we cannot conclude whether rates of disorganized attachment are lower among CSA-exposed school-aged children than among children exposed to other forms of abuse, or whether the relatively lower rates of disorganized attachment in this sample pertain to the field's poorer understanding of disorganized attachment in this age range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in this sample, only 14% of the CSA-exposed children were classified as having disorganized attachment. Previously, researchers have argued that the disorganized attachment classification is in need of additional investigation in terms of how it manifests in middle childhood in general and as measured on the CAI specifically Fearon, Shmueli-Goetz, Viding, Fonagy, & Plomin, 2014;Privizzini, 2017); for instance, some authors suggest that disorganization may present as dismissing attachment later in development (Fearon et al, 2014;Weinfeld, Whaley & Egeland, 2004). However, given the limited number of studies on this topic, at this point we cannot conclude whether rates of disorganized attachment are lower among CSA-exposed school-aged children than among children exposed to other forms of abuse, or whether the relatively lower rates of disorganized attachment in this sample pertain to the field's poorer understanding of disorganized attachment in this age range.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting disorganization of attachment reflects an absence or collapse of strategy for dealing with attachment-related distress (Hesse & Main, 2000;Main & Solomon, 1990), thus increasing risk of psychological difficulties. In middle childhood, researchers can measure children's mental representations of attachment relationships using semi-structured interviews (e.g., the Child Attachment Interview [CAI]; Shmueli-Goetz, Target, Fonagy, & Datta, 2008); an initial validity study of the CAI revealed that 66% of children have secure attachment CSA AND ATTACHMENT IN MIDDLE CHILDHOOD 6 representations, 30% had organized-insecure representations, and 4% of which were classified as having disorganized attachment (see Privizzini, 2017, for a review).…”
Section: Attachmentmentioning
confidence: 99%
“…Important transformations in later stages of development, especially in adolescence, cannot be explained solely by the dynamics of early mother-child interactions. Rather, numerous biopsychosocial factors influence transformations during this particular developmental period (72)(73)(74). In this context, the empirical finding should also briefly mention that some adults in the commonly used Adult Attachment Interview achieve a secure attachment status, but report significant problems from their early relationships with parents.…”
Section: Some Critical Commentsmentioning
confidence: 99%
“…Winnicott (28,29) so inspiringly introduced the psychodynamic concepts of "primary maternal care, " "good enough mothering, " "mirroring, " "holding environment, " and "ability to be alone in the presence of the other" decades ago, into psychoanalytic developmental psychology. His terms today may find their immediate neurobiological correlation in the development of relational and social cerebral maturation (30)(31)(32).…”
Section: Psychobiology Of Early Attachmentmentioning
confidence: 99%
See 1 more Smart Citation